2019
DOI: 10.1155/2019/9797584
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bridge Component Ratings Using Ordinal Logistic Regression Model

Abstract: Prediction of bridge component condition is fundamental for well-informed decisions regarding the maintenance, repair, and rehabilitation (MRR) of highway bridges. The National Bridge Inventory (NBI) condition rating is a major source of bridge condition data in the United States. In this study, a type of generalized linear model (GLM), the ordinal logistic statistical model, is presented and compared with the traditional regression model. The proposed model is evaluated in terms of reliability (the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Ordinal regression models were used to assess the relative influence of the various factors on the project delivery and the plausible strategic measures, which would improve the situation. The ordinal regression model is generally used to forecast the behavior of the ordinal dependent variable (whose values exist on an arbitrary scale) with a set of independent variables [31][32][33]. The dependent variable should be the order response category variable and the independent variables may be categorical or continuous variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinal regression models were used to assess the relative influence of the various factors on the project delivery and the plausible strategic measures, which would improve the situation. The ordinal regression model is generally used to forecast the behavior of the ordinal dependent variable (whose values exist on an arbitrary scale) with a set of independent variables [31][32][33]. The dependent variable should be the order response category variable and the independent variables may be categorical or continuous variables.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable should be the order response category variable and the independent variables may be categorical or continuous variables. It focuses on the strength of the relationships between two or more variables and assumes a dependence or causal relationship between one or more independent variables and one dependent variable [31][32][33]. Furthermore, ordinal regression models offer the advantage to make full use of ranked data [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, each explanatory variable was introduced into the model one by one, and the rationality of the logistic regression model was judged by the significant level of the variables. After the introduction of a new variable, if the variable-2 log-likelihood value is less than the results in the previous step and the pAfter introducing a new variable, if the logarithmic likelihood value of the variable -2 is less than the result of the previous step, and the p value is less than 1%, it indicates that the explanatory variable has a significant correlation with the explanatory variable "on the basis that the major disease insurance is willing to join the commercial major disease insurance," and the logistic regression model "on the basis that the major disease insurance is willing to join the commercial major disease insurance" is reasonable [16][17][18][19][20]. Table 2 shows the regression results in the final step, and the odds ratio reflects the explanatory variables screening process and regression system, the final model includes "health status," "sex," "per capita income," "gender," "age," "education," and "number of children."…”
Section: Intrinsic Constraintsmentioning
confidence: 94%
“…By comparing and analyzing the performance of two models under various conditions, it concluded that the artificial neural network was more suitable for the bridge condition assessment. Lu et al [34] proposed an ordinal logistic regression algorithm for bridge condition assessment.…”
Section: B Bridge Condition Assessment Methodsmentioning
confidence: 99%